The placement of Engiscaptomyza, Grimshawomyia, and Titanochaeta, three clades of endemic Hawaiian Drosophilidae (Diptera) - O’grady, Patrick; Bonacum, James; Desalle, R.; Do Val, Francisca (Zootaxa, 2003)
Based on a combination of molecular and morphological characters, two endemic Hawaiian genera, Titanochaeta Knab and Grimshawomyia Hardy, are transferred to subgenera within the genus Scaptomyza Hardy as is the Drosophila subgenus Engiscaptomyza Kaneshiro. Replacement names for three preoccupied species, Scaptomyza (Titanochaeta) neoevexa O’Grady et al., nom. nov. (for Titanochaeta evaza Hardy), S. (Titanochaeta) neokauaiensis O’Grady et al., nom. nov. (for Titanochaeta kauaiensis Hardy), and S. (Titanochaeta) neosilvicola O’Grady et al., nom. nov. (for Titanochaeta silvicola Hardy), are proposed. This brings the total number of described species in the genus Scaptomyza to 272, of which 141 are endemic to the Hawaiian Archipelago. In comparison, the genus Drosophila contains 368 species endemic to the Hawaiian Islands. Keys for the identification of the Hawaiian subgenera of Scaptomyza and species of Engiscaptomyza, Titanochaeta, and Grimshawomyia are also included.